UTILIZING THE MIT APP INVENTOR TOOLS AS A LEARNING MEDIA INFORMATION TO CREATE ANDROID-BASED APPLICATIONS - Saputra, Ricco Herdiyan; Waziana, Winia (Asia Information System Journal, 2023)
The rapid development of digital technology currently provides many benefits to humans. For example, the development of software or various technological tools that support activities and provide convenience in human life. With the development of the times, software is increasingly sophisticated in various fields, one of which is the field of education. In supporting the learning process, the education sector must follow and adapt existing technology. As is the case with learning media that currently uses an Android-based operating system. Therefore, it is very necessary to educate and teach how to build applications using the operating system. Based on the current problems, the authors provide an educational solution with "Utilization of MIT App Inventor Tools as Learning Media for Creating Android-Based Applications". The data collection technique in this study is a systematic analysis of observations by looking for document similarities. Data collection was also carried out through a literature review by looking for references, journals and documents related to this research. With current technological developments, educational institutions, especially universities, use a lot Android as a means of learning media. As a user of Android, Higher Education also has innovations in studying the provision of materials such as creating various Android-based applications, one of which is the MIT App Inventor. Based on the research process carried out, it can be concluded four things, namely MIT App Inventor is an alternative tool for creating Android-based applications, MIT App Inventor has a visual interface that is easier for ordinary people to learn to use, Visual design in making programs using the method drag-and-drop components, and tools MIT App Inventor also works fine.